The funerary practices in Algeria: An anthropological comparative perspective on burial rituals between muslin and Jewish graves - Soulef, Drici Tani; MILOUDI, Mohamed (The International tax journal, 2025)
This research paper seeks to examine the most important rituals and practices accompanying the burial process between two cultures: Muslims and Jews. It presents the key similarities and differences in burial practices and rituals. This subject has been an extensive field, especially within religious anthropological studies, which aim to uncover what is often left unspoken, from the moment of death to the final stage of burial.